Karakterisasi dan Sifat Biodegradasi Edible Film dari Pati Kulit Pisang Nangka (Musa Paradisiaca L.) dengan Penambahan Kitosan dan Plasticizer Gliserol - Zakiah Drajat Nurfarjin (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2015)
Banana peel is an unused material from the rest of food production that made from banana, have no selling value, and easy to get. A lot content of starch that found in a banana peel can be used as raw material for making edible film which is interesting solutions as a innovative food wrapper. Starch from banana peel were chosen because they can be degraded well, and eatable. Edible films prepared by dissolving starch 10 g in 100 ml of aquadest at a temperature of 65 °C to 70 °C then stirred 1 hour. Chitosan variables are 0,5gr, 1 gr, 2 gr, 2,25gr, and 2,5gr. And glycerol variables are 2ml, 4ml, 5ml, and 6ml. The analysis includes tensile strength and percent elongation. Then continued with the biodegradable analysis for 40 days. Good composition for this edible film are 10 gr starch, 100 ml acetic acid 1%, 2 gr chitosan, and 5 ml glycerol with the result of tensile strength is 43.3953 kg/cm2 and 14 % for percent elongation. Edible film could degraded well at day 28 with the rate of CO2 production 178.2 mg /day. So this edible film proved more eco friendly than synthetic plastic.